Dynamic Combinatorial Chemistry with Novel Dithiol Building Blocks: Towards New Structurally Diverse and Adaptive Screening Collections - Postma, Tobias M.; Galloway, Warren R. J. D.; Cougnon, Fabien B. L.; Pantoş, G. Dan; Stokes, Jamie E.; Spring, David R. (Synlett, 2013)
We describe the synthesis of a range of novel dithiol-functionalized building blocks and demonstrate how they can be used to generate new structurally diverse dynamic combinatorial libraries. A proof-of-principle experiment using the catecholamine dopamine revealed that molecular recognition changed the library composition under biocompatible conditions and identified new promising candidate receptors of this biologically important neurotransmitter.
Keywords: dynamic combinatorial chemistry; thiols; receptors; macrocycles; drugs